TET2-mediated tumor cGAS triggers endothelial STING activation to regulate vasculature remodeling and anti-tumor immunity in liver cancer - Lv, Hongwei; Zong, Qianni; Chen, Cian; Lv, Guishuai; Xiang, Wei; Xing, Fuxue; Jiang, Guoqing; Yan, Bing; Sun, Xiaoyan; Ma, Yue; Wang, Liang; Wu, Zixin; et al. (Nature communications, 2024)
Induction of tumor vascular normalization is a crucial measure to enhance immunotherapy efficacy. cGAS-STING pathway is vital for anti-tumor immunity, but its role in tumor vasculature is unclear. Herein, using preclinical liver cancer models in Cgas / Sting -deficient male mice, we report that the interdependence between tumor cGAS and host STING mediates vascular normalization and anti-tumor immune response. Mechanistically, TET2 mediated IL-2/STAT5A signaling epigenetically upregulates tumor cGAS expression and produces cGAMP. Subsequently, cGAMP is transported via LRRC8C channels to activate STING in endothelial cells, enhancing recruitment and transendothelial migration of lymphocytes. In vivo studies in male mice also reveal that administration of vitamin C, a promising anti-cancer agent, stimulates TET2 activity, induces tumor vascular normalization and enhances the efficacy of anti-PD-L1 therapy alone or in combination with IL-2. Our findings elucidate a crosstalk between tumor and vascular endothelial cells in the tumor immune microenvironment, providing strategies to enhance the efficacy of combinational immunotherapy for liver cancer. Activation of the cGAS-STING pathway has been associated with the promotion of anti-tumor immunity. Here the authors show that TET2 upregulates tumor cGAS to activate STING in endothelial cells, inducing tumor vascular normalization and enhancing efficacy of anti-PD-L1 alone or combined with IL-2 in liver cancer preclinical models.